THE USE OF PROBLEM-BASED LEARNING (PBL) MODEL TO IMPROVE SCIENCE LITERACY SKILLS IN SCIENCE EDUCATION - Annisa Nurul Hasanah; Febriani Sarwendah Asri Nugraheni; Ninik Lestari (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2023)
This research aimed to enhance science literacy skills in the aspect of competence related to interpreting data and scientific evidence using the problem-based learning model in science education at State Junior High School 16 Surakarta. The research method employed is collaborative classroom action research conducted in two cycles. Each cycle comprises four stages: 1) planning, 2) implementation, 3) observation, and 4) reflection. Data collection techniques involve pre-test and post-test questions on science literacy in the aspect of competence related to interpreting data and scientific evidence, consisting of five multiple-choice items in each cycle. The average results of science literacy in the aspect of competence, specifically interpreting data and scientific evidence indicators, in the first cycle were 57.30, and in the second cycle, it increased to 61.15. Based on the research findings, it can be concluded that the problem-based learning model can enhance science literacy skills in the aspect of competence related to interpreting data and scientific evidence in science education at State Junior High School 16 Surakarta.